APPLICATION OF CLEANER PRODUCTION FOR ENVIRONMENTAL MANAGEMENT IN MEZCAUCHOS SAS (2018)
Mezcauchos S.A.S, is a medium-sized manufacturing company with negative environmental impacts in the production of rubber soles. As part of their corporate responsibility, it requires alternatives for an environmental management, through a cleaner production. The environmental impacts are generated in the manufacturing process and are caused by many reasons: raw material waste, water expenditure for the drying process, strong odours in the injection and painting processes. The polyurethane waste is generated in different compositions, as well as the high rates of defective products that must be reprocessed, which brings with it a loss of time, high costs, and unnecessary material expenses, delay of the production process and decreases the profitability. In order to reduce these negative environmental impacts, were developed cleaner production tools that involves alternative solutions like the use of recycling water, the replacement of faucets and flushometers in bathrooms, the maintenance of pipes and connections to the hydraulic network. In addition, the company installed electronic ballasts (T8), 32 W lamps, a RYMEBUS inverter and, movement sensors in bathrooms and corridors. As recommendations that not are installed jet, were found that the company need to establish an appropriate route for the transport and separation of hazardous waste, the installation of containers for disposal, training the personnel for source separation practices. The purchase of a WINTECH injection machine is required to reduce the impact of noise. The internal rate of return (IRR) for the proposed alternatives is 26 % with an annual effective discount rate of 12 %. Copyright © 2018, AIDIC Servizi S.r.l.